Analisis Kinerja Keuangan Lembaga Amil Zakat Nasional Rumah Zakat Periode 2017-2022 - Anisyah, Sarah Siky; Prihatni, Rida; Nasution, Hafifah (LPPM Universitas Negeri Jakarta, 2024)
This study aims to evaluate the financial performance of Rumah Zakat from 2017-2022, using financial ratios established by BAZNAS in 2022. This study is quantitative with secondary data in the form of Rumah Zakat Annual Financial Report 2017-2022. The results of this study indicate that the activity ratio shows high effectiveness, the efficiency ratio shows quite good performance even though there are still challenges in operational costs, the amil fund's ratio shows good performance, and the liquidity ratio shows smooth performance. However, the growth ratio needs to show better performance, so an increase in the collection and distribution of ZIS is needed. In addition, the trend analysis shows an upward trend in the collection and distribution of ZIS funds in 2017-2020, but there was a decrease in 2021 and 2022, which was influenced by the COVID-19, so individuals' ability to pay zakat was limited.